Isolamento compulsório de portadores de hanseníase: memória de idosos The compulsory isolation of Hansen's disease patients: memories of the elderly - Selma Munhoz Sanches de Castro; Helena Akemi Wada Watanabe (História, Ciências, Saúde: Manguinhos)
De 1924 a 1962 o Brasil utilizou a internação compulsória de pacientes de hanseníase como controle da doença na comunidade. Com o final dessa política, muitos pacientes continuaram a viver nessas unidades. O Asilo Pirapitingui, hoje Hospital Dr. Francisco Ribeiro Arantes, é a única retaguarda asilar para internação de portadores de hanseníase por indicação social. Obtivemos o relato da história de vida de oito de seus remanescentes, que foram gravados e transcritos. A análise temática desses relatos permitiu a identificação das seguintes categorias: hanseníase; internação; vida cotidiana; a instituição; condições atuais de saúde; e permanência na instituição após a extinção da internação compulsória. From 1924 to 1962, Brazil used compulsory internment of Hansen's disease patients as one of the ways of controlling the disease in the community. After this policy ended, many patients continued to live in these units. The former Asilo Pirapitingui, now the Hospital Dr. Francisco Ribeiro Arantes, is the only old-style asylum for the socially determined internment of those suffering from Hansen's disease. Through recorded and transcribed interviews of eight of those remaining, we sought to learn their history and the meaning of this isolation in their lives. The thematic analysis of the discourse enabled identification of the following analysis categories: Hansen's disease; internment; day-to-day life; the institution; current health conditions; and staying in the institution after the end of compulsory internment.